Determinan Tingkatan Perilaku Merokok Remaja Kota Kupang - Mesri Welhelmina Nisriani Manafe; Yudith F. Lerrick; Boy S. Effendy (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2019)
Cigarettes are the leading cause of death with 80% of users under the age of 18 worldwide. If this trend continues, it is estimated that five million children under 18 living today will die before becoming adults because they started smoking as a teenager. The aim of the study is to examine the impact of sociodemographic characteristics and social factors on the level of adolescent smoking behavior. The sample was teenagers aged 12-21 who were randomly selected in one (1) junior high school, one (1) high school and one (1) market in Kupang City who were then tested using Ordinal Logistic Regression and Odds Ratio with the Social Cognitive Theory approach. Research results show that sociodemographic characteristic variables through income and gender at a significance level <0.05 affect adolescent smoking behavior, while age predictors have no effect with a significance value of 0.66> 0.05 with the opportunity to become a regular/intermittent/experiment smoker (0.59x, 0.96x, 2x; 0.117x, 0.952x, 1.381x; 9.188x, 2.266x, 4.165x). Variables derived from social factors through peer smoker and paternal smoker affect the smoking behavior of adolescents at the significance level of 0.038 and 0.000 <0.05 and have the chance to become regular/intermittent/experiment smokers (0.160x, 1,282x, 1,538x; 0.052x, 1,088x, 1,088x, 2x).